Persepsi Mahasiswa Kebidanan terhadap Lingkungan Pembelajaran - Setyawati, Irni; Utami, Kusniyati; Soekmawaty Riezqy Ariendha, Dian (Journal of Fundus, 2023)
Background A study programme is a unit of educational activities and the process ofstudent interaction with lecturers and learning resources in a learning environment thathas a certain curriculum and learning methods. The learning environment in question isthe learning process, teaching staff or lecturers, academic achievement, learningatmosphere and social life which is evaluated using the DREEM questionnaireevaluation tool. Method:This study used a descriptive design with a cross-sectionalapproach. The population in this study were all active students in semesters 2, 4, and 6in the midwifery study programme undergraduate academic year 2022/2023. Thesampling technique used total population sampling with a total of 136 people. ResultsData were analysed univariately. Conclusion Most of the midwifery study programmeundergraduate students of STIKes Yarsi Mataram perceived that the learning processwas going well, perceived the model teacher towards lecturers, perceived confidence inacademic achievement, perceived conducive to the learning atmosphere, and perceivedsupportive learning process towards social life.